Penerapan Aplikasi Multisim Pada Mata Kuliah Dasar Elektronika - kamal kamal; Sukirman Sukirman; Nur Alamsyah; Sirwan Sirwan (Universitas PGRI Yogyakarta, 2022)
Learning can be interpreted as a set of plans or patterns that can be used to design learning materials and guide learning activities as a systematic procedure in organizing learning experiences to achieve learning goals. Efforts offered by researchers to improve student learning outcomes by implementing the Multisim Application. This study aims to determine how the process of implementing multisim applications and student learning outcomes in the Basic Electronics course in the Informatics Engineering Study Program, Faculty of Engineering, Islamic University of Makassar. This research is a Quasi Experimental research. The total population is 62 people and the entire population is used as a sample.